Robust Stimulation of Humoral and Cellular Immune Responses following Vaccination with Antigen-Loaded β-Glucan Particles - Haibin Huang (American Society for Microbiology, 2010)
ABSTRACT β-Glucan particles (GPs) are purified Saccharomyces cerevisiae cell walls treated so that they are primarily β1,3-d-glucans and free of mannans and proteins. GPs are phagocytosed by dendritic cells (DCs) via the Dectin-1 receptor, and this interaction stimulates proinflammatory cytokine secretion by DCs. As the hollow, porous GP structure allows for high antigen loading, we hypothesized that antigen-loaded GPs could be exploited as a receptor-targeted vaccine delivery system. Ovalbumin (OVA) was electrostatically complexed inside the hollow GP shells (GP-OVA). Incubation of C57BL/6J mouse bone marrow-derived DCs with GP-OVA resulted in phagocytosis, upregulation of maturation markers, and rapid proteolysis of OVA. Compared with free OVA, GP-OVA was >100-fold more potent at stimulating the proliferation of OVA-reactive transgenic CD8+ OT-I and CD4+ OT-II T cells, as measured by in vitro [3H]thymidine incorporation using DCs as antigen-presenting cells. Next, immune responses in C57BL/6J mice following subcutaneous immunizations with GP-OVA were compared with those in C57BL/6J mice following subcutaneous immunizations with OVA absorbed onto the adjuvant alum (Alum/OVA). Vaccination with GP-OVA stimulated substantially higher antigen-specific CD4+ T-cell lymphoproliferative and enzyme-linked immunospot (ELISPOT) responses than that with Alum/OVA. Moreover, the T-cell responses induced by GP-OVA were Th1 biased (determined by gamma interferon [IFN-γ] ELISPOT assay) and Th17 biased (determined by interleukin-17a [IL-17a] ELISPOT assay). Finally, both the GP-OVA and Alum/OVA formulations induced strong secretions of IgG1 subclass anti-OVA antibodies, although only GP-OVA induced secretion of Th1-associated IgG2c antibodies. Thus, the GP-based vaccine platform combines adjuvanticity and antigen delivery to induce strong humoral and Th1- and Th17-biased CD4+ T-cell responses. IMPORTANCE Most licensed vaccines work by promoting protective antibody responses. However, for many infectious diseases, antibody-mediated protection appears to play a relatively minor role, and vaccination has met with limited success. While live-attenuated organisms generally elicit T-cell responses, their use in vaccines is limited by the potential for causing disease. Thus, there is an urgent need for new vaccine platforms that deliver antigens in such a manner as to promote strong T-cell-mediated responses. Here we designed a novel vaccine platform consisting of yeast-derived β-glucan particles (GPs) that combines antigen delivery and adjuvant activity. GPs loaded with the model antigen ovalbumin (OVA) stimulated robust humoral and T-cell responses in mice. In addition, the cellular response was Th1 and Th17 biased. This work has implications for the design of vaccines that stimulate biased T-cell responses as well as for understanding how immunity to fungal pathogens develops.